(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Androgenetic Alopecia (AGA), or pattern baldness, is a common form of non-scarring hair loss primarily affecting the scalp, with a higher incidence in males. Genetic, hormonal, and environmental factors contribute to its pathogenesis. AGA significantly impacts psychological well-being. Conventional treatments like minoxidil, finasteride, and corticosteroids offer temporary benefits but are associated with adverse effects and recurrence of symptoms, prompting the need for safer alternatives. Methods: A 32-year-old female presented in November 2024 with gradual vertex hair loss and a SALT score of 28%. She was treated for one month with Jalaukavacharana (leech therapy), external application of Shirolepa (herbal paste), and internal Rasayana (rejuvenative) medications. Result: By the end of treatment, the patient showed visible improvement in scalp condition and hair density, with the SALT score reducing to 12%. Discussion: The classical Ayurvedic approach effectively managed AGA by enhancing blood circulation and follicular nourishment, offering a safe and holistic alternative to modern therapies.